1999
DOI: 10.1073/pnas.96.7.3934
|View full text |Cite
|
Sign up to set email alerts
|

Specific association of the gene product of PKD2 with the TRPC1 channel

Abstract: The function(s) of the genes (PKD1 and PKD2) responsible for the majority of cases of autosomal dominant polycystic kidney disease is unknown. While PKD1 encodes a large integral membrane protein containing several structural motifs found in known proteins involved in cell-cell or cell-matrix interactions, PKD2 has homology to PKD1 and the major subunit of the voltage-activated Ca 2؉ channels. We now describe sequence homology between PKD2 and various members of the mammalian transient receptor potential chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
250
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 293 publications
(257 citation statements)
references
References 42 publications
4
250
3
Order By: Relevance
“…This concept was originally proposed by Ma et al [92]. In this study, a yeast two hybrid screen using the C-terminal cytosolic fragment of TRPC1, an interacting protein with PKD2 [11], resulted in the identification of the "a" isoform of the myogenic family (Imfa). I-mfa is a known inhibitor of a subset of bHLHs such as myogenin [93], MyoD [93], and other bHLHs [94].…”
Section: Pkd2-mediated Signal Transductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This concept was originally proposed by Ma et al [92]. In this study, a yeast two hybrid screen using the C-terminal cytosolic fragment of TRPC1, an interacting protein with PKD2 [11], resulted in the identification of the "a" isoform of the myogenic family (Imfa). I-mfa is a known inhibitor of a subset of bHLHs such as myogenin [93], MyoD [93], and other bHLHs [94].…”
Section: Pkd2-mediated Signal Transductionmentioning
confidence: 97%
“…It is now accepted that PKD2 can function at the plasma membrane, but its activity there is under complex regulation involving shuttling between ER and plasma membrane, protein-protein interactions, and modes of activation. Specifically, it has been shown that the amount of PKD2 in the plasma membrane is dynamically regulated by interacting proteins (PKD1 [29,35], Polycystin-2 interactor, Golgi-and ER-associated protein-14 (PIGEA-14) [37]), posttranslational modifications (serine phosphorylation by casein kinase 2 (CK2) [38] and glycogen synthase kinase 3 (GSK3) [39]), interaction with other channel subunits in the plasma membrane (PKD1 [29,35,[40][41][42], TRPC1 [11], TRPV4 [43]) (Fig. 2), and finally, activation secondary to cell surface receptor activation (epidermal growth factor receptor (EGFR) [36]).…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, expression of PKD2 with or without PKD1 in cultured cells produces surface membrane whole-cell currents with nearly linear current-voltage relationships (85,86). It has been shown that PKD2 protein can physically associate with TRPC1 (40). The molecular composition of pore-forming protein(s) underlying the whole-cell currents in PKD2-expressing cells versus the single-channel activity recorded in lipid bilayer deserves further investigation (87).…”
Section: Trp As Mechanosensorsmentioning
confidence: 99%
“…PKD2 (also called TRPP2) was discovered as one of the gene products mutated in autosomal dominant polycystic kidney disease (39). PKD2 is a six-TM protein that shares~25% amino acid identity with the closely related TRPC3 and TRPC6 over the region spanning TM segments IV through VI (40). Mammalian PKD2 is a Ca 2ϩ -permeable, nonselective cation channel (41).…”
Section: The Trpp Subfamilymentioning
confidence: 99%